Softening Hard Water using Cocoa Shell Activated Charcoal - Nurhayati Nurhayati; Ahmil Ahmil; Khairuddin Khairuddin; Tri Handayani; Ahmad Fauzan Tambuak (Jurnal Akademika Kimia, 2021)
Cocoa pod shells contain 23-54 % cellulose, 1.14 % hemicellulose, and 20-27.95 % lignin. The high cellulose content in the cocoa pod shell has the potential to be further processed into adsorbents. Before being used as an adsorbent, activation using HCl solution was carried out to increase the adsorption power of the cocoa shell. This research was conducted to analyze the influence of adsorbent dose, pH solution, the efficiency of hard water reduction, and adsorption capacity on Ca2+ and Mg2+ ions. Adsorption of hard water ions was conducted by varying adsorbent doses of 1, 3, 5, 7, and 9 g and varying at the pH of 5, 6, 7, 8, and 9. Optimum condition achieved at the mass of 5 g with Ca2+ and Mg2+ ions adsorption efficiency of 85.4 and 18.31%, respectively. Optimum condition achieved at the pH of 9 with Ca2+ and Mg2+ ions adsorption efficiency of 61.54 and 49.11%, respectively. The highest Ca2+ and Mg2+ ions adsorption capacity was obtained at the adsorbent mass of 1 g with adsorption capacity respectively 4.05 and 0.54 mg/g. The highest Ca2+ and Mg2+ ions adsorption capacity was obtained at a pH of 9 with an adsorption capacity of 4.05 and 0.54 mg/g, respectively.